IMPLEMENTASI INTEGRASI SOSIAL DAN BUDAYA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA PLUS PARIWISATA - Agus Hermawan; Hilman Mauludin; Akhmad Rojikin; Aceng Nurulhuda (LP2M IAIN Sultan Amai Gorontalo, 2026)
The integration of social and cultural values with Islamic teachings will strengthen the educational process in producing a generation that is not only knowledgeable but also socially aware and culturally adaptable. Islamic education must function as a means of social transformation and strengthening cultural identity based on Islamic values.The purpose of this research is to find out the application of social integration in Islamic religious education, the object of research in this study is SMA Plus Tourism Bandung, the emphasis of this research is qualitative descriptive. The data collection technique is by observation, documentation and interviews, while the data analysis is through reduction, data presentation and conclusion drawn. The data collection technique is using interviews, observations, and documentation. The results of the study show that the application of PAI learning integration with socio-culture at SMA Plus Tourism Bandung is the first of the Integration of PAI Materials with social and cultivated activities through the preparation of syllabus, lesson plans, KD, and indicators that contain local social and cultural values such as mutual cooperation, good manners, and tolerance. The second part of the Learning Strategy covers various social and cultural activities such as social service, PHBI, flash Islamic boarding schools, the use of traditional clothing, and Islamic art practices. This approach fosters social awareness, strengthens the Islamic ukhuwah, and unites Islamic teachings with local traditions. The implementation problems include: Lack of teacher competence, especially in mastery of technology and cultural approaches, second, Lack of synergy and communication between PAI teachers, third, Low interest in learning some students in PAI subjects, fourth, limitations in supervision and evaluation of integrative activities.